2H-azirines as potential bifunctional chemical linkers of cysteine residues in bioconjugate technology - Chen, Yang (2022)
2H-Azirine-2-caboxamides have been designed to perform as a new type of bifunctional thiol linker under very mild reaction conditions. The cleavage of a C-N double bond of 2H-azirine furnishes an amino amide functional group in situ through a thiol addition and ring-opening process. It works with a broad scope of thiols and 2H-azirines in the absence of any catalysts at room temperature. Cysteine-containing peptides have also been demonstrated to work efficiently in a completely water solution.